2008
DOI: 10.1007/s00125-008-0993-0
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for skeletal muscle caveolin-1 as an insulin sensitivity modulator in ageing-dependent non-obese type 2 diabetes: studies in a new mouse model

Abstract: Aims/hypothesis Type 2 diabetes mellitus is a common agedependent disease. We discovered that male offspring of non-diabetic C57BL/6 and DBA/2 mice, called JYD mice, develop type 2 diabetes when they grow old. JYD mice show characteristics of insulin resistance, hyperglycaemia and hyperinsulinaemia in old age without obesity. We postulated that the mechanism of age-dependent type 2 diabetes in this model relates to caveolin-1 status in skeletal muscle, which appears to regulate insulin sensitivity in the mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 37 publications
4
33
1
Order By: Relevance
“…We previously found that male, but not female, JYD mice developed type 2 diabetes in old age, and that reduced levels of caveolin-1 were correlated with the development of diabetes in male mice (18). In the present study, we investi-…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…We previously found that male, but not female, JYD mice developed type 2 diabetes in old age, and that reduced levels of caveolin-1 were correlated with the development of diabetes in male mice (18). In the present study, we investi-…”
Section: Introductionmentioning
confidence: 60%
“…JYD F1 mice were obtained from mating female C57BL/6 and male DBA/2 mice, as previously described (18). Mice were given free access to food and water, except when noted otherwise, and were kept on a cycle of 12-h light/12-h dark at 23°C and 65% humidity.…”
Section: Animalsmentioning
confidence: 99%
“…Although the mechanisms of signaldependent regulation in the caveolae remain unclear, our results indicate that IRa and IRS1 are positively regulated by CAV1 in muscle cells. Consistent with these results, an increase in Cav1 expression in skeletal muscle improves insulin sensitivity (Cohen et al 2004, Oh et al 2008. Conversely, Cav1-null mice displayed skeletal muscle abnormalities due to tubular aggregate formation (Schubert et al 2007) and exercise intolerance (Razani et al 2001), demonstrating that insulin/IGF signaling depends on the level of Cav1 expression in muscle.…”
Section: Discussionmentioning
confidence: 75%
“…In humans, CAV1 mutations cause generalized lipodystrophy, insulin resistance, and hypertriglyceridemia (Gazzerro et al 2010). Moreover, we have demonstrated that the level of CAV1 in skeletal muscle is related to insulin sensitivity in vitro and in vivo (Oh et al 2008), indicating that CAV1 may regulate insulin signaling. Notably, Cav1-deficient mice have a lean phenotype (Razani et al 2002).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation